EGFR activation triggers cellular hypertrophy and lysosomal disease in NAGLU-depleted cardiomyoblasts, mimicking the hallmarks of mucopolysaccharidosis IIIB - De Pasquale, Valeria; Pezone, Antonio; Sarogni, Patrizia; Tramontano, Alfonso; Schiattarella, Gabriele Giacomo; Avvedimento, Vittorio Enrico; Paladino, Simona; Pavone, Luigi Michele (Cell death & disease, 2018)
Mucopolysaccharidosis (MPS) IIIB is an inherited lysosomal storage disease caused by the deficiency of the enzyme α- N -acetylglucosaminidase (NAGLU) required for heparan sulfate (HS) degradation. The defective lysosomal clearance of undigested HS results in dysfunction of multiple tissues and organs. We recently demonstrated that the murine model of MPS IIIB develops cardiac disease, valvular abnormalities, and ultimately heart failure. To address the molecular mechanisms governing cardiac dysfunctions in MPS IIIB, we generated a model of the disease by silencing NAGLU gene expression in H9C2 rat cardiomyoblasts. NAGLU-depleted H9C2 exhibited accumulation of abnormal lysosomes and a hypertrophic phenotype. Furthermore, we found the specific activation of the epidermal growth factor receptor (EGFR), and increased phosphorylation levels of extracellular signal-regulated kinases (ERKs) in NAGLU-depleted H9C2. The inhibition of either EGFR or ERKs, using the selective inhibitors AG1478 and PD98059, resulted in the reduction of both lysosomal aberration and hypertrophy in NAGLU-depleted H9C2. We also found increased phosphorylation of c-Src and a reduction of the hypertrophic response in NAGLU-depleted H9C2 transfected with a dominant-negative c-Src. However, c-Src phosphorylation remained unaffected by AG1478 treatment, posing c-Src upstream EGFR activation. Finally, heparin-binding EGF-like growth factor (HB-EGF) protein was found overexpressed in our MPS IIIB cellular model, and its silencing reduced the hypertrophic response. These results indicate that both c-Src and HB-EGF contribute to the hypertrophic phenotype of NAGLU-depleted cardiomyoblasts by synergistically activating EGFR and subsequent signaling, thus suggesting that EGFR pathway inhibition could represent an effective therapeutic approach for MPS IIIB cardiac disease.